Application of the Snowball Throwing Type Cooperative Learning Model to Improve Students' Mathematics Learning Outcomes at MIS Tarbiyatul Islamiyah Tanjunganom - Utami, Wahyu; Pratama, Wahyu Putra Marga Aji; Astuti, Welly; Nahrowi, Wawi; Jannah, Wardatul (Jurnal Cendekia Islam Indonesia, 2025)
This study aims to examine the application of the Snowball Throwing type cooperative learning model to improve students' mathematics learning outcomes at MIS Tarbiyatul Islamiyah Tanjunganom. The research method used is classroom action research (CAR) with two cycles, involving sixth-grade students. The research procedure includes planning, implementation, observation, and reflection in each cycle. Data were collected through learning outcome tests, observations, and interviews to analyze the effectiveness of the Snowball Throwing model in mathematics learning. The results show that the implementation of the Snowball Throwing model can increase student engagement, communication among students, and understanding of mathematical concepts. Before the model was implemented, the average test score of students was 65, while after the implementation in the second cycle, the average test score increased to 85. Thus, it can be concluded that the Snowball Throwing model is effective in improving students' mathematics learning outcomes at MIS Tarbiyatul Islamiyah Tanjunganom.